Experimental tests of co-combustion of laying hens manure with coal by using thermogravimetric analysis. (October 2017) - Junga, Robert; Knauer, Waldemar; Niemiec, Patrycja; Tańczuk, Mariusz
Abstract: Waste from poultry farming, apart from good fertilizing properties, can be also a valuable source of energy. The article refers to the possibility of using laying hens manure burned separately or with gas-flame coal. In this research elemental and proximate analyses were used, as well as the heating values for characterization of the fuels properties. Furthermore, simultaneous Thermogravimetric and Differential Thermal Analyses (TG-DTA) were performed for separate biomass and coal samples and also for their blends containing 25, 50 and 75% by weight of poultry. The reaction regions as well as the ignition characteristics, burnout and maximal temperatures of analysed fuels were detected. The study demonstrates the significant differences in the composition and the character of combustion of both fuels. With the biomass content increase the reduction of the ignition temperature was observed, thereby increasing of the reactivity of the sample. The activation energy was calculated with the use of model-free isoconversional Ozawa-Flynn-Wall method (OFW). Average Activation Energy E α was much higher for biomass (128.6 kJ/mol) than for coal (21.6 kJ/mol), whereas for blends E α was increasing with the biomass content increase. Synergy exists between the two components in the main combustion region. Highlights: Coal and laying hens manure have significantly different thermal profiles. Laying hens manure is more reactive than gas-flame coal. Average activation energy for blends were lower than for raw biomass sample. Synergies between coal and laying hens occur in the main combustion zone.